“Drive Your Career”: Strategi Meningkatkan Adaptabilitas Karier Melalui Pelatihan Karier - Doddy Hendro Wibowo; Emmanuel Satyo Yuwono (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2021)
Career problems experienced by students may indicate that they do not understand their potential, lack of career information, choose wrong majors, doubt about career choices, and do not have a career yet. The purpose of this study is to determine whether the